10h-29=61

Simple and best practice solution for 10h-29=61 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10h-29=61 equation:


Simplifying
10h + -29 = 61

Reorder the terms:
-29 + 10h = 61

Solving
-29 + 10h = 61

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '29' to each side of the equation.
-29 + 29 + 10h = 61 + 29

Combine like terms: -29 + 29 = 0
0 + 10h = 61 + 29
10h = 61 + 29

Combine like terms: 61 + 29 = 90
10h = 90

Divide each side by '10'.
h = 9

Simplifying
h = 9

See similar equations:

| 64x^2+192x+9=0 | | 2c+3x+5m+4x+m= | | 3m+16=4m+9 | | 15p^4+8p^2=-26p^3 | | 3(x+2.05)=2x | | 9=7x+3(-4x) | | c^2-16x=x^2-2x-1 | | X=Y+W | | X+0.20X=100 | | 5x+1.5=13 | | g-23.8=4.4g | | X^2-8=10 | | X+0.15X=100 | | 4t=5t^2 | | X-VSQUARED=WSQUARED | | 4y-114=14 | | -2=-7u+3(u+2) | | 6+5(1-6x)=131 | | -4-8=-20 | | -5(2x-6)+8x= | | z^6+2z^3-6iz^3=11+2i | | 7x-5=-75 | | 6+3=27 | | -7+2=10y-7-9y | | 6x(x+9)=(2x+8)(x+9) | | 6X^2+7x=-1 | | y=2r | | x^2+2x-6ix=11+2i | | 2x+4=-5(x+5) | | -9(9x+9)+4= | | 24=2w+6(w-4) | | -4-4x=-44 |

Equations solver categories